2020
DOI: 10.1186/s11671-020-03424-8
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Power Conversion Efficiency of Quantum Dot-Sensitized Solar Cells by Integrating Concentrating Photovoltaic Concept with Double Photoanodes

Abstract: Despite great efforts dedicated to enhance power conversion efficiency (PCE) of quantum dot-sensitized solar cells (QDSSCs) in the past two decades, the efficiency of QDSSCs is still far behind its theoretical value. The present approaches for improving PCE are mainly focused on tailoring the bandgap of QDs to broadening light-harvesting and optimizing interfaces of component parts. Herein, a new solar cell architecture is proposed by integrating concentrating solar cell (CPV) concept into QDSSCs with double p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Furthermore, the radii of the second circles of the black TiO 2 based photoanodes are remarkably smaller than those of the pristine TiO 2 , corresponding to the smaller charge transfer resistance, which indicates that the charge transport of black TiO 2 -based devices is faster than that of pristine TiO 2 -based photoanodes. This is due to oxygen vacancy doping providing a more convenient transport channel for electrons [ 8 , 35 ]. This greatly improves the ability of the TiO 2 thin film to separate, collect, and transport photogenerated carriers in the cell, thereby reducing the loss of the photogenerated carriers during the device operation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the radii of the second circles of the black TiO 2 based photoanodes are remarkably smaller than those of the pristine TiO 2 , corresponding to the smaller charge transfer resistance, which indicates that the charge transport of black TiO 2 -based devices is faster than that of pristine TiO 2 -based photoanodes. This is due to oxygen vacancy doping providing a more convenient transport channel for electrons [ 8 , 35 ]. This greatly improves the ability of the TiO 2 thin film to separate, collect, and transport photogenerated carriers in the cell, thereby reducing the loss of the photogenerated carriers during the device operation.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Therefore, there is still a long way to go to improve the photoelectric performance of QDSSCs by further optimizing their components. In QDSSCs, the photoanode, as an important part, provides the attachment site for quantum dots and a fast channel for photogenerated carriers to transfer to the external circuit, 24–26 so the photoanode plays an irreplaceable role. As shown in Table S1,† researchers have achieved better research results by selecting or optimizing different photoanodes in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies adopting this strategy have demonstrated improved PCEs, such as CdSe 0.2 S 0.8 /CdMnSe, 11 CdS/InSb, 12 CuInSe 2 /Mg–CdS, 13 and CdS/CdSe. 14 In the alloying strategy, the bandgap can be tailored by adjusting the compositions of the constituent cation or anion elements separately (cation or anion alloying) or in combination (combined cation/anion alloying). Many studies have demonstrated the effectiveness of alloying in enhancing the photovoltaic performance of QDSSCs.…”
Section: Introductionmentioning
confidence: 99%